The Effect of Abusive Supervision on Employee Silence with Perceptions of Organizational Politics and Organizational Justice as Mediation - Sulastri, Iis; Wulansari, Nury Ariani (Universitas Negeri Semarang, 2018)
The purpose of this study is to explain the effect of abusive supervision on employee silence with perceptions of organizational politics and organizational justice as mediator. The population of this study was all employees of a developing textile and garment company in the Semarang District. The sampling method used a multi-stage random sampling with a sample of 199 respondents. Methods of data collection used observation, interviews and questionnaires that were measured using a Likert scale. Methods of analysis of this study used the software of WarpPLS 6.0. The results show that abusive supervision and perceptions of organizational politics have a positive effect on employee silence. abusive supervision has a positive effect on perceptions of organizational politics, but abusive supervision has a negative effect on organizational justice. In addition, organizational justice has a negative effect on employee silence. Perceptions of organizational politics and organizational justice as a partial mediating role on the effect of abusive supervision on employee silence. Suggestions for the company that the company can reduce the high of employee silence with giving treatment employees fairly and supervisor should improve its supervision system.